High prevalence of venous thrombotic events in Cushing's syndrome: data from ERCUSYN and details in relation to surgery - Isand, Kristina; Feelders, Richard; Brue, Thierry; Toth, Miklos; Deutschbein, Timo; Reincke, Martin; Kršek, Michal; Santos, Alicia; Demtröder, Frank; Chabre, Olivier; Strasburger, Christian J; Aulinas Maso, Anna; et al. (European journal of endocrinology, 2024)
OBJECTIVE: The aim of this study was to evaluate the prevalence of venous thromboembolism (VTE) in patients included in the European Registry on Cushing's syndrome (ERCUSYN), compare their clinical characteristics with those who did not develop VTE and identify risk factors for VTE. DESIGN: A retrospective observational cohort study. METHODS: Data extraction from the registry was taken on February, 7, 2022. At the time there were 2174 patients diagnosed with Cushing's syndrome (CS) and 95 VTEs were reported in the database. RESULTS: Of 95 VTE events 70 (74%) were in pituitary-dependent CS patients, 12 (12.5%) in adrenal-dependant CS, 10 (10.5%) in ectopic CS, and 3 (3%) in CS due to other causes. Sex, 24-hour urinary free cortisol (UFC) value at diagnosis, as well as the number of operations remained statistically significant predictors of VTE. Of patients who were treated with at least one surgery, 12 (13%) VTE occurred before and 80 (87%) after the surgery. Nearly half of these VTEs occurred within six months since the operation (36; 45%). Over half of the centers that reported VTE did not routinely anticoagulate CS patients. Anticoagulation schemes varied widely. CONCLUSION: Patients with CS have an elevated risk of developing VTE for an extended period of time. From ERCUSYN cohort patients have higher risk for VTE if they need multiple surgeries to treat CS, are males and have high UFC values at the diagnosis of CS. Since there is no agreement on thromboprohpylaxis, a protocol for VTE prevention that is widely adopted appears to be necessary for patients with CS.
Keywords: žilní tromboembolie; Cushingův syndrom; Female; Prevalence; hypersekrece ACTH v hypofýze; ženské pohlaví; hydrokortison; Venous Thromboembolism; lidé; trombóza; Hydrocortisone; prevalence; retrospektivní studie; Male; Pituitary ACTH Hypersecretion; Thrombosis; Cushing Syndrome; mužské pohlaví; Retrospective Studies; Humans